The Pharisees - Sievers, Joseph 1948-; Levine, Amy-Jill 1956- (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2021)
"A multidisciplinary appraisal of who the Pharisees were, what they taught, and how they have been understood and depicted throughout history"--
Includes index
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Pharisees; Aufsatzsammlung